Liver progenitor cells in massive hepatic necrosis: how can a patient survive acute liver failure? - Lin, Tao; Feng, Rilu; Liebe, Roman; Weng, Honglei (Biomolecules, 2022)
Massive hepatic necrosis is the most severe lesion in acute liver failure, yet a portion of patients manage to survive and recover from this high-risk and harsh disease syndrome. The mechanisms underlying recovery remain largely unknown to date. Recent research progress highlights a key role of liver progenitor cells, the smallest biliary cells, in the maintenance of liver homeostasis and thus survival. These stem-like cells rapidly proliferate and take over crucial hepatocyte functions in a severely damaged liver. Hence, the new findings not only add to our understanding of the huge regenerative capability of the liver, but also provide potential new targets for the pharmacological management of acute liver failure in clinical practice.